Preferential trade agreements, investment disciplines and investment flows - Hoekman, Bernard (2005)
Reviews the potential impacts of preferential trade agreements (PTAs) on investment. Compares recent agreements with a focus on provisions in bilateral US and EU agreements. Examines some of the evidence to date on the investment effects of PTAs.